Study of the Influence of Leadership, Organizational Climate, Commitment and Lecturer Creativity on Quality Management in Higher Education - Sutja, Akmal; Hamdi, Muhamad; Yaksa, Rully Andi; Muspawi , Mohammad (Migration Letters, 2024)
The low-performance accountability score of Jambi University in Indonesia in 2022 was the starting point for this research. This influence study aims to determine the magnitude of the influence of leadership, organizational climate, commitment, and creativity of lecturers on the quality management of higher education. This research uses an associative quantitative approach with an explanatory survey method using regression and path analysis, a research population of 620, and a sample of 86 with a stratified random sampling technique. The number of questionnaires is 105, and they are conducted through statistical assumption tests of normality, homogeneity, and linearity. The research results show that there is an influence of leadership, organizational climate, and commitment to quality management of higher education simultaneously at 58.8% (strong), with details of leadership influence 66.88% (very strong), organizational climate 12.49 (low but sure), commitment 16.27 (quite strong ) while lecturer creativity 0.43% (very weak) does not have a significant influence on the quality management of higher education, based on research findings, the recommendations given are the development of leadership training, building a quality culture and customer satisfaction-oriented commitment, creating a creativity laboratory.